2017
DOI: 10.1167/iovs.17-21723
|View full text |Cite
|
Sign up to set email alerts
|

Functional Activity of Matrix Metalloproteinases 2 and 9 in Tears of Patients With Glaucoma

Abstract: [PXG]). These were compared to patients undergoing cataract surgery (controls) for this cross-sectional study. Functional activities of tear MMP-9 and MMP-2 were analyzed by gelatin zymography. Tenon's capsules (n ¼ 15) were harvested from the inferior quadrant in those undergoing cataract surgery and protein expression of MMP-9 was analyzed by immunohistochemistry (IHC). Hydrogen peroxide (H 2 O 2 ) stress-induced effects on in vitro activities of MMP-9 in human trabecular meshwork (HTM) cells were analyzed.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 16 publications
1
49
1
5
Order By: Relevance
“…The posterior particles gelling would hinder the drug diffusion from its inner core to the release media leading to a low release fashion extended for three additional days [76,77]. In vitro release studies were also performed in media containing protease or MMP-2 at the equivalent concentrations observed on the ocular surface in glaucomatous patients suffering inflammation events [53][54][55]. According to our data, these nanoparticles were resistant to these media, being able to protect the active compound and to progressively release it even at these conditions, probably due to the high density of the crosslinked gelatin matrix [78].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The posterior particles gelling would hinder the drug diffusion from its inner core to the release media leading to a low release fashion extended for three additional days [76,77]. In vitro release studies were also performed in media containing protease or MMP-2 at the equivalent concentrations observed on the ocular surface in glaucomatous patients suffering inflammation events [53][54][55]. According to our data, these nanoparticles were resistant to these media, being able to protect the active compound and to progressively release it even at these conditions, probably due to the high density of the crosslinked gelatin matrix [78].…”
Section: Discussionmentioning
confidence: 99%
“…Formulations were physicochemically characterized. In order to mimic ocular surface conditions, the in vitro release tests were performed with proteases or metalloproteinase-2 (MMP-2) in the release media, which are enzymes typically present in the eye of glaucomatous patients [53][54][55]. These results were compared with conventional release studies performed with plain PBS solutions.…”
Section: Introductionmentioning
confidence: 99%
“… A number of studies have found that MMP‐9 in biologic fluids, such as blood, urine, synovial fluid, and gingival crevicular fluid, are a diagnostic marker of local and systemic diseases including cardiovascular diseases; pulmonary disease; rheumatoid arthritis; and osteoarthritis; ophthalmologic diseases such as cataracts and glaucoma; sepsis and mortality; and periodontitis …”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have found that MMP-9 in biologic fluids, such as blood, urine, synovial fluid, and gingival crevicular fluid, are a diagnostic marker of local and systemic diseases including cardiovascular diseases 2,3,19,20 ; pulmonary disease 18,21 ; rheumatoid arthritis; and osteoarthritis [22][23][24] ; ophthalmologic diseases such as cataracts and glaucoma 25,26 ; sepsis and mortality 27 ; and periodontitis. 28 MMP-9 is now known to have multiple biological effects beyond its originally recognized ability to degrade denatured collagen fragments (gelatin) and basement membrane (type IV) collagen.…”
Section: Discussionmentioning
confidence: 99%
“…Our earlier study on HTM cell lines showed de nite morphological differences apart from differential MMP expressions with varying time period of exposure to oxidative stress re ecting that cell death mechanisms may be different with different severity of the insult. 23 Yet, the exact molecular mechanisms in-vivo regulating cell death/functioning in the TM tissue at different stages of glaucoma is not yet elucidated.This study explores the differential role of cell death process in the TM in different stages of glaucoma.…”
Section: Introductionmentioning
confidence: 99%